Carbohydrate metabolism in cerebral stroke patients - T. V. Volchenkova; I. G. Kolchu; Ye. V. Isakova; S. V. Kotov (Бюллетень сибирской медицины)
Early carbohydrate disturbances (ECD) influence cerebral stroke development and course. Prevalence and co-morbidity of different carbohydrate metabolism types were studied in 107 cerebral stroke patients. It was determined that different disturbances developed in 70% of cerebral stroke patients. Even ECD negatively affected cerebral stroke course.